2008
DOI: 10.1113/expphysiol.2007.040204
|View full text |Cite
|
Sign up to set email alerts
|

Co‐localization of angiotensin‐converting enzyme 2‐, octomer‐4‐ and CD34‐positive cells in rabbit atherosclerotic plaques

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a novel enzyme with possible implications in the treatment of blood pressure disorders. Recent evidence suggests that an upregulation of ACE2 can be stimulated by all-trans retinoic acid (at-RA); however, at-RA also affects regulation of the stem-cell marker octomer-4 (Oct-4) and thus cellular differentiation. We have previously shown that smooth muscle cells and macrophages present within rabbit atherosclerotic plaques are positive for ACE2, Oct-4 and the haematopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…24 In this study, we found that ATRA could up-regulate the expression of ACE2 and could inhibit the expression of angiotensin I, ACE1 and angiotensin II. Zulli et al 25 found that ATRA could stimulate ACE2 expression in rabbit atherosclerotic plaques. Zhong et al 24 found that chronic ATRA treatment increased the gene and protein expression of ACE2, resulting in the reduction of blood pressure and the attenuation of myocardial damage in spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…24 In this study, we found that ATRA could up-regulate the expression of ACE2 and could inhibit the expression of angiotensin I, ACE1 and angiotensin II. Zulli et al 25 found that ATRA could stimulate ACE2 expression in rabbit atherosclerotic plaques. Zhong et al 24 found that chronic ATRA treatment increased the gene and protein expression of ACE2, resulting in the reduction of blood pressure and the attenuation of myocardial damage in spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on its cellular distribution in atherosclerosis show that ACE2 is expressed in endothelial cells (ECs) [34,35], vascular smooth muscle cells (VSMCs) [29,34] and macrophages [29,34,35]. Gene over-expression studies show that overexpression of ACE2 by gene transfer can attenuate the progression of atherosclerotic lesions when the ACE2 gene is transferred four weeks after injury in a rabbit model of atherosclerosis [29].…”
Section: Existence and Function Of Ace2 In Experimental Atherosclerosismentioning
confidence: 98%
“…ACE2 is expressed in atherosclerosis in experimental animals [29,34,35]. Studies on its cellular distribution in atherosclerosis show that ACE2 is expressed in endothelial cells (ECs) [34,35], vascular smooth muscle cells (VSMCs) [29,34] and macrophages [29,34,35].…”
Section: Existence and Function Of Ace2 In Experimental Atherosclerosismentioning
confidence: 99%
“…Also, at-RA affects regulation of the stem cell marker octomer-4 (Oct-4) and eventually, cellular differentiation. Zulli et al [ 27 ] showed that cells within atherosclerotic plaques of New Zealand White rabbits co-express ACE2 and the hematopoietic stem cell marker, CD34. Thus, at-RA treatment could affect plaque cellular biology via effects on cellular differentiation and blood pressure via its effect on ACE2 [ 27 ].…”
Section: Pharmacologic and Hormonal Ace2 Modulationmentioning
confidence: 99%